Mangrove reforestation tests in a semiarid coastal swamp of Yucatán, México - Febles-Patrón, José Luis; Novelo López, Jorge; Batllori Sampedro, Eduardo (Instituto de Ecología, A.C., 2016)
Rhizophora mangle L. (red mangrove) and Avicennia germinans (L.) L. (black mangrove) seedling survival and growth were evaluated in reforestation trials as part of an environmental restoration and regional development program in the Chabihau coastal microbasin, Yucatan, Mexico. Building of road bridges over inlets modified swamp conditions by increasing tide reflux and reducing salinity extremes. Mangrove seedling survival is now regulated by flood level and growth by salinity. Red mangrove survival was highest in deeper areas and with higher development with lower soil salinity (3 ,28 psu ± 0,32 psu), while black mangrove survival was higher in shallower areas and development was highest with higher soil salinity (45,5 psu ± 0,50 psu). Building of sediment beds to control degree of flooding aided in increasing black mangrove survival, and clearing of springs to reduce salinity ensured proper growth. Survival was higher for nurseryraised red mangrove seedlings than for directly planted red mangrove seedlings. High black mangrove natural incorporation was probably favored by the lower water depth and higher salinity in the swamp during 2006, a low rainfall year. Reforestation programs need to include monitoring of surface and soil hydrological parameters (especially flood level and salinity) to aid in the selection of optimum species and methods for higher seedling survival and improved growth.